Digital media, literacies and African literature - Pier Paolo Frassinelli; Lisa Treffry-Goatley (The Thinker)
In this article, we explore the impact of digital media on African literacy practices and literature. As our starting point, we want to problematise the notion that digital media spell doom for reading generally and for African literature in particular. Versions of this argument include perturbations that ‘African readerships are under siege’ by ‘the cost of books, varying degrees of general literacy, inadequate library services and the seductions of the web and social media’ (Ojwang and Titlestad, 2014)